MicroRNA-181a-5p antisense oligonucleotides attenuate osteoarthritis in facet and knee joints. Issue 1 (4th October 2018) - Nakamura, Akihiro; Rampersaud, Yoga Raja; Nakamura, Sayaka; Sharma, Anirudh; Zeng, Fanxing; Rossomacha, Evgeny; Ali, Shabana Amanda; Krawetz, Roman; Haroon, Nigil; Perruccio, Anthony V; Mahomed, Nizar N; Gandhi, Rajiv; et al.
Abstract : Objectives: We recently identified microRNA-181a-5p (miR-181a-5p) as a critical mediator involved in the destruction of lumbar facet joint (FJ) cartilage. In this study, we tested if locked nucleic acid (LNA) miR-181a-5p antisense oligonucleotides (ASO) could be used as a therapeutic to limit articular cartilage degeneration. Methods: We used a variety of experimental models consisting of both human samples and animal models of FJ and knee osteoarthritis (OA) to test the effects of LNA-miR-181a-5p ASO on articular cartilage degeneration. Histopathological analysis including immunohistochemistry and in situ hybridisation were used to detect key OA catabolic markers and microRNA, respectively. Apoptotic/cell death markers were evaluated by flow cytometry. qPCR and immunoblotting were applied to quantify gene and protein expression. Results: miR-181a-5p expression was increased in human FJ OA and knee OA cartilage as well as injury-induced FJ OA (rat) and trauma-induced knee OA (mouse) cartilage compared with control cartilage, correlating with classical OA catabolic markers in human, rat and mouse cartilage. We demonstrated that LNA-miR-181a-5p ASO in rat and mouse chondrocytes reduced the expression of cartilage catabolic and chondrocyte apoptotic/cell death markers in vitro. Treatment of OA-induced rat FJ or mouse knee joints with intra-articular injections of in vivo grade LNA-miR-181a-5p ASO attenuated cartilage destruction, and the expression of catabolic, hypertrophic, apoptotic/cell death and type II collagen breakdown markers. Finally, treatment of LNA-miR-181a-5p ASO in cultures of human knee OA chondrocytes (in vitro) and cartilage explants (ex vivo) further demonstrated its cartilage protective effects. Conclusions: Our data demonstrate, for the first time, that LNA-miR-181a-5p ASO exhibit cartilage-protective effects in FJ and knee OA.